2023
DOI: 10.1530/joe-23-0095
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 10 alleviates acute lung injury by inhibiting excessive autophagy via Nrf2

Abstract: Acute lung injury (ALI) is associated with an increased incidence of respiratory diseases, which are devastating clinical disorders with high global mortality and morbidity. Evidence confirms that fibroblast growth factors (FGFs) play key roles in mediating ALI. Mice adapted treatment with LPS (lipopolysaccharide; 5 mg/kg, intratracheally) to establish in vivo ALI model. Human lung epithelial BEAS-2B cells cultured in a corresponding medium with LPS were performed to mimic ALI model in vitro. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…23,24 Studies have shown that inhibiting LPS-induced excessive autophagy in alveolar epithelial cells can mitigate inflammatory injury. 25,26 Moreover, excessive autophagy activation has been implicated in the development of ALI, [27][28][29][30] and the effective inhibition of autophagy is a potential therapeutic approach. Thus, modulating autophagy from inducing death to supporting survival could prove effective in the treatment of LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Studies have shown that inhibiting LPS-induced excessive autophagy in alveolar epithelial cells can mitigate inflammatory injury. 25,26 Moreover, excessive autophagy activation has been implicated in the development of ALI, [27][28][29][30] and the effective inhibition of autophagy is a potential therapeutic approach. Thus, modulating autophagy from inducing death to supporting survival could prove effective in the treatment of LPS-induced ALI.…”
Section: Introductionmentioning
confidence: 99%